Mediating Vulnerability Comparative approaches and questions of genre - Masschelein, Anneleen; Mussgnug, Florian; Rushworth, Jennifer (Comparative Literature and Culture, 2021)
Mediating Vulnerability examines vulnerability from a range of connected perspectives. It responds to the vulnerability of species, their extinction but also their transformation. This tension between extreme danger and creativity is played out in literary studies through the pressures the discipline brings to bear on its own categories, particularly those of genre. Extinction and preservation on the one hand, transformation, adaptation and (re)mediation on the other. These two poles inform our comparative and interdisciplinary project. The volume is situated within the particular intercultural and intermedial context of contemporary cultural representation. Vulnerability is explored as a site of potential destruction, human as well as animal, but also as a site of potential openness. This is the first book to bring vulnerability studies into dialogue with media and genre studies. It is organised in four sections: 'Human/Animal'; Violence/Resistance'; 'Image/Narrative'; and 'Medium/Genre'. Each chapter considers the intersection of vulnerability and genre from a comparative perspective, bringing together a team of international contributors and editors. The book is in dialogue with the reflections of Judith Butler and others on vulnerability, and it questions categories of genre through an interdisciplinary engagement with different representational forms, including digital culture, graphic novels, video games, photography and TV series, in addition to novels and short stories. It offers new readings of high-profile contemporary authors of fiction including Margaret Atwood and Cormac McCarthy, as well as bringing lesser-known figures to the fore.